Analisis Jenis Kalimat pada Teks Prosedur dalam Buku Teks Dasar-Dasar Teknik Pesawat Udara SMK/MAK Kelas X Kurikulum Merdeka - M. Andhika Pebrian; Muhammad Fahmi Nurhadi; Galan Anugerah Novanto; Alfarell Fadhil Waradana; Asep Purwo Yudi Utomo; Diyamon Prasandha (CV. Aksara Global, 2023)
This study aims to analyze the types of sentences in procedure texts in the textbook Basics of Aircraft Engineering Class X SMK/MAK Independent Curriculum. The population of this study is the five procedure texts contained in the presentation of the material for the book Basics of Aircraft Engineering for Class X SMK/MAK Independent Curriculum on pages 45th to 47th and 49th to 50th. The data collection technique used was the reading and note-taking technique, while the study method used the matching method. Data analysis was carried out using a descriptive method and the technique used was the referential equivalent technique. The results of the study include the following sentences. First, types of sentences based on purpose, namely, imperative sentences and declarative sentences. Second, the types of sentences based on the way of presentation, namely, the release sentences and the climax sentences. Based on the analysis that has been done, it was found that the most commonly used types of sentences in the five procedure texts contained in the textbook Basics of Aircraft Engineering SMK/MAK Class X Independent Curriculum are imperative sentences and climax sentences, but other types of sentences are also found in the form of declarative sentences and release sentences.